The JURNAL ANALISIS PEMBENAHAN SISTEM KOMPENSASI BERBASIS KEMENTERIAN KETENAGAKERJAAN UKM AYAM GORENG BOGOR - Ovi Apricilia; Rahmi Yudesti; Ita' Rahmah Wati; Abel Zaki Zufar; Lindawati Kartika (KOLEGIAL, 2023)
Abstract The effective development of a compensation system is an important factor in maximizing human resource management in small and medium enterprises (SMEs). The object of this research is Ayam Goreng Bogor SME, a fast-food culinary SME in Bogor Regency. The purpose of this study is to identify the compensation system of Ayam Goreng Bogor SME, to identify compensable factors of compensation for the SME, to analyze the factors underlying the creation of the salary calculation structure, and to analyze an ideal compensation system applied. This research uses a quantitative descriptive method. The analysis of the compensation system improvement in this study uses two methods, Adhered and Overlapping. The calculation of the salary structure for Ayam Goreng Bogor SME is based on formal education, work experience, customer focus and responsiveness, communication skills, physical effort, integrity, teamwork, initiative, work conditions, and customer service orientation. Based on the results of the discussion, the ideal compensation system for Ayam Goreng Bogor SME is by using the Overlapping method. Keywords: adhered, compensation, overlapping, salary structure, sme.